Effect of Diclofenac and Simvastatin on Bone Defect Healing—An In Vivo Animal Study - Theodora Karanikola; Angeliki Cheva; Katia Sarafidou; Maria Myronidou-Tzouveleki; Ioannis Tsavdaridis; Eleana Kontonasaki; Anastasios Tsirlis (Biomimetics, 2022)
Non-steroidal, anti-inflammatory drugs and statins are two widely prescribed drug classes that affect bone formation. The aim of this study was to elucidate the effect of diclofenac and simvastatin in artificial bone defect healing. One hundred and forty-four male Wistar rats were used, and the specimens were divided into groups, with respect to the route of drug administration and the type of defect healing (with or without collagen membrane), and subgroups, with respect to the study duration (2, 4 or 8 weeks). Diclofenac was intramuscularly administered while simvastatin was administered both systemically and locally. Animals were euthanized and specimens were histomorphometrically analyzed to evaluate the percentage of new bone formation (%). Bone healing that occurred without any intervention developed more steadily than that of all other groups. Diclofenac exerted a clear, direct inhibitory effect on bone healing and its systemic administration should be avoided. The systemic administration of simvastatin was related to severe myopathy, while the solvent for the local administration of simvastatin seemed to play significant role in bone growth, as simvastatin, when it is administered intraperitoneally in a DMSO solution, appeared to promote bone healing. Local administration may have a significant impact on bone healing and it should be further investigated with the type of solvent or carrier that is used, which both may play a significant role in bone repair induction.